Teaching the dynamics of the growth of a business venture through transparent simulations - Capelo, C. (2021)
Achieving rapid and sustainable growth is essential for business ventures to succeed. This being so, future entrepreneurs need to understand and manage the dynamics of business growth. Simulation-based learning environments (SBLEs) have been proposed as effective tools to help learners improve their understanding of complex business problems. However, previous research has found that learners tend to underestimate dynamic complexity. Transparent simulations allow entrepreneurship learners to explore the dynamic complexity of business ventures while accessing the model structure and growth behaviour. Previous studies have addressed some aspects of model transparency and produced inconclusive results regarding their impact on learning effectiveness. This study explores the learning and performance effects of using transparent simulations to teach the dynamics of the growth of a business venture. One such simulation experiment used a system dynamics model that represented the development of an energy service company (ESCO) venture under varying conditions of simulator transparency. Students who were subjected to the more transparent strategy achieved higher performance and demonstrated better comprehension of the business dynamics. However, our findings indicate that the effect to be gained from making only the simulator model more visible is more limited. The structural debriefing (focused on the critical variables and relations) was determinant in improving students’ learning regarding the stocks and flows structure in the prospects pipeline. Only after participating in the behavioural debriefing (focused on the relation between model structure, patterns of actions, and system behaviour), were the students able to appreciate the dynamics of the business feedback loops. The research suggests that educators who use complex business simulations should complement model transparency with structural and behavioural debriefings.